Atypical Evolution of the F1Fo Adenosine Triphosphate Synthase Regulatory ATP6 subunit in Glacier Ice Worms (Annelida: Clitellata: Mesenchytraeus). (12th July 2018) - Lang, Shirley A; Shain, Daniel H
The glacier ice worm, Mesenchytraeus solifugus, is among a few animals that reside permanently in glacier ice. Their adaptation to cold temperature has been linked to relatively high intracellular adenosine triphosphate (ATP) levels, which compensate for reductions in molecular motion at low physiological temperatures. Here, we show that ATP6—the critical regulatory subunit of the F1Fo-ATP synthase and primary target of mitochondrial disease—acquired an unprecedented histidine-rich, 18-amino acid carboxy-terminal extension, which counters the strong evolutionary trend of mitochondrial genome compaction. Furthermore, sequence analysis suggests that this insertion is not of metazoan origin, but rather is a product of horizontal gene transfer from a microbial dietary source, and may act as a proton shuttle to accelerate the rate of ATP synthesis.